2020
DOI: 10.1038/s41598-020-78886-y
|View full text |Cite
|
Sign up to set email alerts
|

K2P2.1 (TREK-1) potassium channel activation protects against hyperoxia-induced lung injury

Abstract: No targeted therapies exist to counteract Hyperoxia (HO)-induced Acute Lung Injury (HALI). We previously found that HO downregulates alveolar K2P2.1 (TREK-1) K+ channels, which results in worsening lung injury. This decrease in TREK-1 levels leaves a subset of channels amendable to pharmacological intervention. Therefore, we hypothesized that TREK-1 activation protects against HALI. We treated HO-exposed mice and primary alveolar epithelial cells (AECs) with the novel TREK-1 activators ML335 and BL1249, and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 111 publications
0
15
0
Order By: Relevance
“…Studies of K 2P function have uncovered that members of this family are important for diverse classes of physiological responses and pathological conditions such as action potential propagation, 15 , 16 anesthetic responses, 17 , 18 microglial surveillance, 19 sleep duration, 20 pain, 21 23 arrhythmia, 24 ischemia, 17 , 25 , 26 cardiac fibrosis, 27 depression, 28 migraine, 29 intraocular pressure regulation, 30 pulmonary hypertension, 31 and lung injury. 32 Due to their unusual topology, diverse gating stimuli, and poor pharmacology, K 2P s have remained the most poorly understood potassium channel class. 8 , 9 , 33 35 Nevertheless, the structures of six homomeric K 2P s are now known ( Figure 1 (a) ) 36 41 and reveal a conserved overall architecture that defines the K 2P family ( Figure 1(c) and (d) ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of K 2P function have uncovered that members of this family are important for diverse classes of physiological responses and pathological conditions such as action potential propagation, 15 , 16 anesthetic responses, 17 , 18 microglial surveillance, 19 sleep duration, 20 pain, 21 23 arrhythmia, 24 ischemia, 17 , 25 , 26 cardiac fibrosis, 27 depression, 28 migraine, 29 intraocular pressure regulation, 30 pulmonary hypertension, 31 and lung injury. 32 Due to their unusual topology, diverse gating stimuli, and poor pharmacology, K 2P s have remained the most poorly understood potassium channel class. 8 , 9 , 33 35 Nevertheless, the structures of six homomeric K 2P s are now known ( Figure 1 (a) ) 36 41 and reveal a conserved overall architecture that defines the K 2P family ( Figure 1(c) and (d) ).…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the resulting tensions of the cell membranes may activate mechanosensitive channels. TREK-1 was reported to be expressed in alveolar epithelial cells [182,183], contribute to the reaction to hyperoxia [184,185], and modulate inflammatory mediator (interleukin-6, monocyte chemotactic protein-1) release [186,187]. It has also been suggested that TREK-1 modulates stretch-induced detachment of alveolar epithelial cells [188].…”
Section: Physiological Role Of the Mechanical Activation Of K 2p Channels In Other Locationsmentioning
confidence: 99%
“…Furthermore, BL1249 has previously been validated to be specifically active in the TREK-1 channel, not only in heterologous expression systems but also in primary cells (20,21), which act on a gating mechanism involving a site located below the selectivity filter and the C-type gate (2). However, there is no study investigating whether bepridil can affect BL1249-activated TREK-1 current.…”
Section: Original Articlementioning
confidence: 99%